Solve for z (z+5)-2(4z-1)=0

Math
(z+5)-2(4z-1)=0
Simplify (z+5)-2(4z-1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
z+5-2(4z)-2⋅-1=0
Multiply 4 by -2.
z+5-8z-2⋅-1=0
Multiply -2 by -1.
z+5-8z+2=0
z+5-8z+2=0
Simplify by adding terms.
Tap for more steps…
Subtract 8z from z.
-7z+5+2=0
Add 5 and 2.
-7z+7=0
-7z+7=0
-7z+7=0
Subtract 7 from both sides of the equation.
-7z=-7
Divide each term by -7 and simplify.
Tap for more steps…
Divide each term in -7z=-7 by -7.
-7z-7=-7-7
Cancel the common factor of -7.
Tap for more steps…
Cancel the common factor.
-7z-7=-7-7
Divide z by 1.
z=-7-7
z=-7-7
Divide -7 by -7.
z=1
z=1
Solve for z (z+5)-2(4z-1)=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top